Increased Work Productivity Through Bibliometric Analysis - Suryadi, Suryadi; Hoeroni, Rizqon (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In an era of ever-evolving research, a deep understanding of work productivity is crucial to improving the performance of individuals, institutions, and the research field as a whole. This study explores the potential use of bibliometric analysis as an effective tool in analyzing and improving work productivity and by using the VOSViewer application to be able to find improvements in work productivity in the period 2019 to 2024. This approach allows us to look beyond the number of publications, taking into account factors such as h index, citation rate, and collaboration patterns. This article data was obtained from the Goggle Schooler database using the Publish or Perish reference manager application. From this search, there are 200 articles that are considered relevant. These results show that the number of publications related to this topic from 2019 to 2024 is fairly large. With an average number of publications.